Origin and Function of Monocytes in Inflammatory Bowel Disease - Liao X; Liu J; Guo X; Meng R; Zhang W; Zhou J; Xie X; Zhou H (Dove Medical Press, 2024)
Xiping Liao,1,2,* Ji Liu,3,* Xiaolong Guo,1 Ruiping Meng,1 Wei Zhang,1 Jianyun Zhou,1 Xia Xie,1,2 Hongli Zhou1 1Clinical Medical Research Center, the Second Affiliated Hospital, Army Medical University, Chongqing, People's Republic of China; 2Department of Gastroenterology, the Second Affiliated Hospital, Army Medical University, Chongqing, People's Republic of China; 3Sun Yat-sen University Cancer Center, State Key Laboratory of Oncology in South China, Guangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Xia Xie, Department of Gastroenterology, the Second Affiliated Hospital, Army Medical University, No. 83 Xinqiao Main Street, Shapingba District, Chongqing, 400037, People's Republic of China, Email xiexia0128@163.com Hongli Zhou, Clinical Medical Research Center, the Second Affiliated Hospital, Army Medical University, No. 83 Xinqiao Main Street, Shapingba District, Chongqing, 400037, People's Republic of China, Email zhouhli7@mail2.sysu.edu.cnAbstract: Inflammatory bowel disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), is a chronic disease resulting from the interaction of various factors such as social elements, autoimmunity, genetics, and gut microbiota. Alarmingly, recent epidemiological data points to a surging incidence of IBD, underscoring an urgent imperative: to delineate the intricate mechanisms driving its onset. Such insights are paramount, not only for enhancing our comprehension of IBD pathogenesis but also for refining diagnostic and therapeutic paradigms. Monocytes, significant immune cells derived from the bone marrow, serve as precursors to macrophages (M&phis;s) and dendritic cells (DCs) in the inflammatory response of IBD. Within the IBD milieu, their role is twofold. On the one hand, monocytes are instrumental in precipitating the disease's progression. On the other hand, their differentiated offsprings, namely moM&phis;s and moDCs, are conspicuously mobilized at inflammatory foci, manifesting either pro-inflammatory or anti-inflammatory actions. The phenotypic spectrum of these effector cells, intriguingly, is modulated by variables such as host genetics and the subtleties of the prevailing inflammatory microenvironment. Notwithstanding their significance, a palpable dearth exists in the literature concerning the roles and mechanisms of monocytes in IBD pathogenesis. This review endeavors to bridge this knowledge gap. It offers an exhaustive exploration of monocytes' origin, their developmental trajectory, and their differentiation dynamics during IBD. Furthermore, it delves into the functional ramifications of monocytes and their differentiated progenies throughout IBD's course. Through this lens, we aspire to furnish novel perspectives into IBD's etiology and potential therapeutic strategies.Keywords: IBD, monocytes, inflammatory response